Anti-Corruption Declaration as a Measure of Control for the Activities of Subjects of Public Authorities - Корнута, Людмила Михайлівна; Корнута, Л. М.; Корнута, Людмила Михайловна; Kornuta, Liudmyla M.; Kornuta, Liudmila; Голоядова, Тетяна Олексіївна; Голоядова, Т. О.; Голоядова, Татьяна Алексеевна; Holoiadova, Tetiana O.; Goloyadova, Tetiana; Завгородня, Юлія Володимирівна; Завгородня, Ю. В.; et al. (Dorma Trading, 2020)
The article is devoted to the study of anti-corruption declaration in Ukraine, which is at the stage of institutionalization and practical improvement. The aim of the article is to establish possible ways to increase the effectiveness of the anti-corruption declaration mechanism, taking into account socio-economic conditions based on the use of international experience in this process; to define a single concept of the humanization of the financial control and identify specific recommendations for reforming the existing system of anti-corruption mechanism in Ukraine. In carrying out this study, general and special methods of scientific knowledge were used: the system analysis method, the dialectic method, the formal logical method and the structural-functional method, as well as a number of empirical methods. The authors came to the conclusion that the mechanism of anti-corruption declaration in Ukraine was formed taking into account the socio-economic prerequisites for counteracting corruption and international trends in the implementation of financial control. To increase the positive effect of the introduction of anti-corruption declaration, it is important to know the approach chosen for exercising financial control over the subjects of public administration. The article may be useful for the relevant subjects of public administration for the further improvement of socially sensitive anti-corruption tools. It may also be useful for researchers of social and legal processes related to the development of civil society. An analysis of the processes of management transformation in the country and in the world facilitated to identify problems that require special attention and find solutions for the implementation of project activities to create a modern management structure for electronic filing of declarations. The novelty and originality of the study lies in the fact that the article reveals the fundamental determinants of anti-corruption declaration taking into account the development trends of public administration.

Стаття присвячена дослідженню декларації про боротьбу з корупцією в Україні, яка знаходиться на етапі інституціоналізації та практичного вдосконалення. Метою статті є встановлення можливих шляхів підвищення ефективності механізму антикорупційного декларування з урахуванням соціально-економічних умов, заснованих на використанні міжнародного досвіду в цьому процесі; визначення єдиної концепції гуманізації фінансового контролю та конкретних рекомендацій щодо реформування існуючої в Україні системи антикорупційного механізму. При проведенні цього дослідження були використані загальні та спеціальні методи наукового пізнання: метод системного аналізу, діалектичний метод, формально-логічний та структурно-функціональний метод, а також ряд емпіричних методів. Автори дійшли висновку, що механізм антикорупційного декларування в Україні сформований з урахуванням соціально-економічних передумов протидії корупції та міжнародних тенденцій у здійсненні фінансового контролю. Для посилення позитивного ефекту від запровадження антикорупційної декларації важливо знати підхід, обраний для здійснення фінансового контролю за суб’єктами державного управління. Стаття може бути корисною для відповідних суб’єктів державного управління для подальшого вдосконалення соціально відчутних інструментів боротьби з корупцією. Вона також може бути корисною для дослідників соціальних та правових процесів, пов'язаних з розвитком громадянського суспільства. Аналіз процесів трансформації управління в країні та світі сприяв виявленню проблем, що потребують особливої ​​уваги, та пошуку рішень для реалізації проектної діяльності для створення сучасної структури управління для електронної подачі декларацій. Новизна та оригінальність дослідження полягає в тому, що в статті розкриваються основні детермінанти антикорупційної декларації з урахуванням тенденцій розвитку державного управління.

Статья посвящена исследованию декларации о борьбе с коррупцией в Украине, которая находится на этапе институционализации и практического совершенствования. Целью статьи является установление возможных путей повышения эффективности механизма антикоррупционного декларирования с учетом социально-экономических условий, основанных на использовании международного опыта в этом процессе; определение единой концепции гуманизации финансового контроля и конкретных рекомендаций по реформированию существующей в Украине системы антикоррупционного механизма. При проведении этого исследования были использованы общие и специальные методы научного познания: метод системного анализа, диалектический метод, формально-логический и структурно-функциональный метод, а также ряд эмпирических методов. Авторы пришли к выводу, что механизм антикоррупционного декларирования в Украине сформирован с учетом социально-экономических предпосылок противодействия коррупции и международных тенденций в осуществлении финансового контроля. Для усиления положительного эффекта от внедрения антикоррупционной декларации важно знать подход, выбранный для осуществления финансового контроля за субъектами государственного управления. Статья может быть полезна для соответствующих субъектов государственного управления для дальнейшего совершенствования социально ощутимых инструментов борьбы с коррупцией. Она также может быть полезной для исследователей социальных и правовых процессов, связанных с развитием гражданского общества. Анализ процессов трансформации управления в стране и мире способствовал выявлению проблем, требующих особого внимания, и поиска решений для реализации проектной деятельности для создания современной структуры управления для электронной подачи деклараций. Новизна и оригинальность исследования заключается в том, что в статье раскрываются основные детерминанты антикоррупционной декларации с учетом тенденций развития государственного управления.
Kornuta L. Anti-Corruption Declaration as a Measure of Control for the Activities of Subjects of Public Authorities / L. Kornuta, T. Goloyadova, Yu. Zavhorodnia, Yu. Reva // Journal of Environmental Treatment Techniques. – V. 8 (4). - Dorma Trading, 2020. – P. 1504-1509.
Keywords: Corruption; Humanization; Anti-corruption declaration; Subject of public authority; Financial control; International standards; корупція; гуманізація; антикорупційна декларація; суб’єкт державної влади; фінансовий контроль; міжнародні стандарти; коррупция; гуманизация; антикоррупционная декларация; субъект государственной власти; финансовый контроль; международные стандарты; Research Subject Categories::LAW/JURISPRUDENCE